Resistance Training Volume Enhances Muscle Hypertrophy but Not Strength in Trained Men - Schoenfeld, Brad J; Contreras, Bret; Krieger, James; Grgic, Jozo; Delcastillo, Kenneth; Belliard, Ramon; Alto, Andrew (Medicine and science in sports and exercise, 2019)
The purpose of this study was to evaluate muscular adaptations between low-, moderate-, and high-volume resistance training protocols in resistance-trained men. Thirty-four healthy resistance-trained men were randomly assigned to one of three experimental groups: a low-volume group performing one set per exercise per training session (n = 11), a moderate-volume group performing three sets per exercise per training session (n = 12), or a high-volume group performing five sets per exercise per training session (n = 11). Training for all routines consisted of three weekly sessions performed on nonconsecutive days for 8 wk. Muscular strength was evaluated with one repetition maximum (RM) testing for the squat and bench press. Upper-body muscle endurance was evaluated using 50% of subjects bench press 1RM performed to momentary failure. Muscle hypertrophy was evaluated using B-mode ultrasonography for the elbow flexors, elbow extensors, mid-thigh, and lateral thigh. Results showed significant preintervention to postintervention increases in strength and endurance in all groups, with no significant between-group differences. Alternatively, while all groups increased muscle size in most of the measured sites from preintervention to postintervention, significant increases favoring the higher-volume conditions were seen for the elbow flexors, mid-thigh, and lateral thigh. Marked increases in strength and endurance can be attained by resistance-trained individuals with just three 13-min weekly sessions over an 8-wk period, and these gains are similar to that achieved with a substantially greater time commitment. Alternatively, muscle hypertrophy follows a dose-response relationship, with increasingly greater gains achieved with higher training volumes.